Animation : the mechanics of motion - Webster, Chris (Focal Press visual effects and animation series., 2005)
"A guide to all the fundamental principles of animation. With extended pieces on timing, acting and technical aspects Chris Webster has created a learning tool to help you get the most out of your animation and to develop the practical skills needed by both professionals and serious students alike."--Jacket